Hubungan Antara Pola Asuh Demokratis dengan Kreativitas pada Siswa Sekolah Menengah X di Kabupaten Bantul - Juni Wulan Ningsih; Indra Wahyudi; FX. Wahyu Widiantoro (Jurnal Psikologi, 2021)
The purpose of this research to knowing relationship between democratic parenting and creativity on student of Art Vocational High School in Kasihan Bantul. The subjects of this researh is student of SMK N 3 Kasihan Bantul (SMSR), 15 to 18 years of ages amounting to 61 persons. Metodological research is using Figural Creativity Test and Democratic parenting scale. The analyze of the data in this reasearch is using Product Moment Correlation from Karl Pearson with spss 20 for windows. Based on correlation of the analysis is obtained rxy = -0,083 with p = 0,524. This suggest that there is no relation between democratic parenting and creativity on student of Art Vocational High School in Kasihan Bantul or SMKN 3 Kasihan Bantul.